Promoting and strengthening public health through undergraduate education - Walker, Ali (Can J Public Health, 2019)
There are widely divergent views as to what constitutes “public health” and “public health research”. But regardless of these views, readers of this journal would likely agree that public health matters; we assert that so does the educational programming that prepares its workforce. Our voiced perspectives as authors are influenced by our respective training, occupations, and academic locales, and we believe that undergraduate public and population health education (UGPPHE) across many disciplines is crucial to strengthening public health in Canada. Existing literature and discourse related to UGPPHE in Canada tends to be concentrated around its ancillary positioning within clinical health disciplines such as medicine, nursing, and dentistry, rather than on the evolution of undergraduate degree programs. While UGPPHE programming has the important function of preparing undergraduates to enter into practice as public health professionals, it has added virtue in its capacity to improve public health literacy and produce a more robust body of informed and engaged citizens. The intent of this commentary is to draw increased attention towards the other disciplines less well known for bringing awareness to UGPPHE in Canada and to commence what will hopefully be a cascade of dialogue from stakeholders across the nation.